The origins of Christian morality the first two centuries - Meeks, Wayne A. (New Haven, CT Yale UP, 1993)
Incudes bibliographical references and indexes
Keywords: Christian ethics -- history -- early church, ca.30-600.; Ethics in the Bible; Bible. N.T. -- criticism, interpretation, etc; Sociology, Biblical